Numerical and experimental investigation of flow phenomena in rotating step-holes for direct-spray-cooled electric motors. (May 2021) - Beck, Christopher; Schorr, Jürgen; Echtle, Harald; Verhagen, Jasmin; Jooss, Annette; Krüger, Christian; Bargende, Michael
Despite their high efficiency, electric motors are thermally limited in some operating points by several types of losses. Whenever temperature–critical components threaten to overheat, the performance is reduced for component protection (derating). The use of a suitable cooling concept may reduce the derating. The design of efficient cooling concepts of electric motors in traction drives with increased power densities is challenging, caused by the fact that the heat releases in the components vary considerably with the operating point. One option to reduce the temperatures is to place the heat sinks close to heat sources. Therefore, direct spray cooling with nozzles located in the rotor shaft is often used for cooling the end windings. The dielectric fluid (e.g. oil) is introduced into the mainly air-filled interior of the electric motor. In the following study, the behavior of the jet in the rotating step-holes at different volumetric flow rates is examined. To carry out the investigation, a new test rig and a novel optically accessible electric motor were designed. In this specifically designed test environment, the shape of the jets of different operating points is investigated by direct high-speed visualization. The cinematography setup is made of a four-light-emitting diode system in combination with a high-speed camera. A combined approach of experiment and simulation is used to find basic mechanisms of spray formation produced by rotating step-holes. Depending on the volumetric flow rate and the rotational speed, the direction of the oil jet gets more curved in relation to the rotating nozzle after exiting the small bore. If the deflection is large, the jet impinges on the wall of the large bore before reaching the end of the nozzle. The jet formation at the exit of the step-hole is mainly driven by the divergent forces in the liquid caused by impingement and the counteracting Coriolis force. Depending on the volumetric flow rate with constant rotational speed, different cross-sectional shapes of the jet at the exit are observed. These characteristic shapes can be grouped as a round undisturbed jet, strands with a connecting lamella and a C-shaped cross-section.